Duas maneiras de “domar” o mercado: por que Hegel precisa da polícia e das corporações (Revista Eletrônica Estudos Hegelianos, 2020)
The article examines some aspects of Hegel’s economic thought in his account of civil society, especially in his Philosophy of Right. It presents Hegel’s proposal of an economic and a sociological way for taming the destabilizing aspects of free market and for inserting universality into it. These two models are based on the institutions of police (Polizei) and corporation (Korporation), respectively. Hegel refuses a purely economic view of the market, which considers individual preferences as given, only influenced by a change in its institutional framework, as defended already by Adam Smith and taken up in the 1990s by Karl Homann. Instead, Hegel argues that people’s choices are formed by their social contexts, opening the way for the sociological approach promoted against Homann by Peter Ulrich, influenced by Jürgen Habermas. Whereas the measures taken by the police act on the individuals through a purely external framework, Hegel advocates that the corporations shape individuals in a thoroughgoing way. These institutions are crucial for the formation (Bildung) of the individuals’ preferences and identities and, therefore, for the development of an ethos that brings order into civil society and secures the ground for the full ethos of political citizenship.